Fresh concrete consistency effect on thin-walled columns creep phenomenon - MADUREIRA,E. L. (2018)
Abstract A concrete structural member when kept under sustained load presents progressive strains over time, associated to the material creep. The fresh concrete consistency, specially, exerts some effect on that phenomenon. The pioneering formulations developed to modelling the creep of concrete are applicable, directly, to the cases for which the stress magnitude remains constant. Its application to reinforced concrete structural members, that exhibits changes in the magnitude of the stresses over such a time dependent phenomenon, requires simplifications from which result the memory models, whose implementation presents the disadvantage of involving the history of the stresses storage. The State Models were developed to overcome these difficulties, as they result of integral calculus scheme improvement, dispensing such computational memory storage. The subject of this work is the analysis of creep strains on reinforced concrete thin-walled columns, emphasizing the fresh concrete consistency efecct, on the base of a state model, fixing the values of its physical parameters from the NBR 6118/14 proceedings [1]. The obtained results showed the occurrence of stresses transfer from the mass of the concrete to the reinforcement steel bars, that was more pronounced in those cases for which the slump test abatement were the highest and, in some cases, including, it induced the material yielding condition.